Abstract machines : Samuel Beckett and philosophy after Deleuze and Guattari - Dowd, Garin (Faux titre, 2007)
"What can philosophy bring to the reading of Beckett? Combining intertextual analysis with a 'schizoanalytic genealogy' derived from the authors of L'Anti-Oedipe, Garin Dowd's Abstract Machines: Samuel Beckett and Philosophy after Deleuze and Guattari offers an innovative response to this much debated question. The author focuses on zones of encounter and thresholds of engagement between Beckett's writing and a range of philosophers (among them Spinoza, Leibniz and Kant) and philosophical concepts. Becketts writing impacts in a variety of ways on Deleuze and Guattaris thought, and, in particular, resonates with Deleuze's contributions to the history of philosophy (in books such as Le Pli: Leibniz et le baroque), and his 'critical and clinical' approach to literature. Furthermore, the books co-written with Guattari, concerned as they are with the 'molecularization' of the discipline of philosophy in the name of 'thinking otherwise', reveal themselves in a new light when explored in conjunction with Becketts oeuvre. With its arresting perspectives on a wide range of Beckett's works, Abstract Machines will appeal to academics and postgraduate students interested in the philosophical aspects of his writing."--Jacket